Bioactive polyketides and meroterpenoids from the mangrove-derived fungus Talaromyces flavus TGGP35 - Cai, Jin; Zhou, Xueming; Wang, Bin; Zhang, Xuelong; Luo, Mengyao; Huang, Longtao; Wang, Ruoxi; Chen, Yonghao; Li, Xiaoyang; Luo, Youping; Chen, Guangying; Cao, Fei; et al. (Frontiers in Microbiology, 2024)
Six new polyketides, including three new lactones talarotones A-C (1-3), one new polyketide talarotide A (4), two new polyenes talaroyenes A-B (5-6), along with one new meroterpenoid talaropenoid A (7), and thirteen known compounds (8-20) were isolated from the mangrove-derived fungus Talaromyces flavus TGGP35. The structures and absolute configurations of 1-7 were elucidated by detailed HR-ESI-MS, IR, 1D/2D NMR spectroscopic data, Mo2(OAc)4-induced electronic circular dichroism (ECD), calculated ECD data, CD spectroscopy, and modified Mosher's method. Compounds 5 and 20 showed antioxidant activity with the IC50 values of 0.40 and 1.36 mM, respectively. Compounds 3, 6, 11 and 16-17 displayed cytotoxic activity against human cancer cells Hela, A549, with IC50 values ranging from 28.89-62.23 μM. Compounds 7, 10-12, 14-18 exhibited moderate or potent anti-insect activity against newly hatched larvae of Helicoverpa armigera Hubner, with IC50 values from 50-200 μg/mL. Compound 18 showed antibacterial activity against Ralstonia solanacearum with the MIC value of 50 μg/mL.